Evaluation of Cytomorphological Patterns of Fibroadenoma on Cytology: Emphasis on Pattern based approach to avoid misdiagnosis (Bangladesh Journal of Medical Science, 2022)
Background: Fibroadenoma (FA) is a frequently occurring breast lesion diagnosed on fine needle aspiration cytology (FNAC) with a bimodal picture comprising of epithelial and/or stromal component. It can have a gamut of differential diagnosis depending on the predominant cellular features reflected on cytological smears, thereby it is important that the cytologist should be well versed with the various patterns of fibroadenoma to avoid diagnostic errors.Materials and methods: The present study was conducted over a period of two years including all cases of fibroadenoma diagnosed on cytology (n=234). The detailed cytomorphological spectrum was analysed to study the different patterns of fibroadenoma on cytology. Out of these (234), cytohistological correlation was performed in 197 cases.Results: The incidence of fibroadenoma among all the breast FNACs was 50% (234/468). The different patterns observed were: epithelial predominant, stromal predominant, FA with giant cells, apocrine change, cyst macrophages, granuloma, acute inflammation and atypia. Cytohistologic concordance was observed in 173/197 cases (87.8%). Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were 98.8%, 92.3%, 87.8%, 94.5% and 88.8% respectively.Conclusion: Although fibroadenoma can be diagnosed with ease on cytology in most of the cases, However, at times in addition to classical features, morphological variations are observed such as giant cells, cyst macrophages, apocrine change, granulomas, acute inflammation and atypia wherein it maybe misdiagnosed as benign phyllodes, hyperplasia, fibrocystic disease etc.. This pattern based approach for the cytological diagnosis of FA is re-emphasized in the index article so as to create awareness about these varied patterns among the young cytopathologists.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 590-595